2019
DOI: 10.3390/w11122635
|View full text |Cite
|
Sign up to set email alerts
|

Field Testing of Porous Pavement Performance on Runoff and Temperature Control in Taipei City

Abstract: The Taipei University of Technology, under contract from the Taipei City Government, completed a study on porous asphalt (PA) and permeable interlocking concrete brick (PICB) pavement performance with respect to stormwater runoff reduction and surface temperature mitigation. Additionally, the variation of infiltration rates against time of these pavements was monitored. The results show the following: (a) Runoff peak reduction ranged from 16% for large, intense storms to 55% for small, long-duration storms. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 8 publications
2
30
0
2
Order By: Relevance
“…This study agrees with previous studies [ 17 , 23 , 26 , 28 , 29 ] which found that the temperature at each depth changed basically synchronously with the air temperature are shown in Figure 4 and Figure 5 . Amplitudes of pavements temperature variations decreased while the depth increased.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This study agrees with previous studies [ 17 , 23 , 26 , 28 , 29 ] which found that the temperature at each depth changed basically synchronously with the air temperature are shown in Figure 4 and Figure 5 . Amplitudes of pavements temperature variations decreased while the depth increased.…”
Section: Resultssupporting
confidence: 93%
“…Even though temperatures of the porous asphalt pavement were rapidly increasing as air temperatures increase, but the temperature of the porous asphalt pavement was rapidly decreasing as air temperatures decrease. Consistent with results of Cheng et al [ 28 ], porous pavements had lower temperature than those for traditional pavements on very hot days. Thus, the large-scale applications of porous pavements could help mitigate urban heat island impacts.…”
Section: Introductionsupporting
confidence: 91%
“…A perforated pipe is optional at the top of the base to bypass the excessive inflow for avoiding waterlogging. Typical permeable pavements include interlocking permeable pavers; soil-filled grid pavers; porous asphalt slab; porous concrete slab [67,68]. Design of these permeable pavements can be referred elsewhere, e.g.…”
Section: Permeable Pavementsmentioning
confidence: 99%
“…The performance of porous asphalt (PA) and permeable interlocking concrete bricks (PICB) was evaluated in terms of hydraulics and thermal properties (Cheng, Lo, Ho, Lin, & Yu, 2019). Runoff peak flow reductions varied from 16% to 55% for large high-intensity storms and smaller long-duration storms, respectively.…”
Section: Hydraulics and Related Propertiesmentioning
confidence: 99%